Serial mediation of perceived quality and customer engagement on brand image and online purchase intention of premium hotels in China-a conceptual paper / Wong Chee Hoo, Liu Xioayan and Kumarashvari Subramaniam - Chee Hoo, Wong; Xioayan, Liu; Subramaniam, Kumarashvari (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Brand image, customer engagement, and perceived quality are key variables influencing customer behaviours in premium hotels online booking. Brand image as a cognitive perspective drives customer behaviours to an online website. Premium hotels always have a clear position and unique brand image, but whether it, directly and indirectly, affects the online booking behaviour of customers deserves a detailed study. Moreover, Customer engagement attracts customers and stimulates booking behaviours too. However, not much is known as to whether there is a significant relationship between the premium brand image and customer online engagement and whether customer engagement affects booking intention. Besides, perceived quality is the customer-driven perspective to evaluate or perceived a product. Service quality is the measurement of how customers perceived service quality as against their expectations. Thus, this paper is undertaken to examine the serial mediation of perceived quality and customer engagement with the direct relationship between brand image and purchase intention by using an online survey. A sample size of 384 respondents will be collected using the probability sampling technique to fill in this gap found in the literature.